Peran Ma’had Putri dalam Penerapan Integrasi Ilmu Agama dan Sains di UIN Malang dan Dampaknya Terhadap Penguatan Karakter Mahasantri - Annisa Nuril Faradisa; Imron Rossidy (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The integration of religious studies and science has become an important paradigm in modern Islamic education, including at the Maulana Malik Ibrahim State Islamic University (UIN) in Malang. However, the application of this integration at Ma'had Putri has not been studied in depth, especially in terms of how the development process is carried out and the extent of its impact on the character of female students. This study aims to analyze the role of Ma'had Putri in the application of the integration of religious and scientific knowledge and to identify its impact on the character building of female students. The study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation involving caregivers, Musyrifah, and female students. The results of the study show that Ma'had Putri internalizes the integration of knowledge through habitual worship, book studies, taklim afkar, mentoring, and activities that connect religious teachings with scientific understanding. The caregivers play a role in directing the vision of guidance, while the musyrifah (female supervisors) become the main companions in instilling discipline and spirituality. Meanwhile, the mahasantri (female students) understand integration as an effort to connect religious teachings with the phenomena they encounter in their daily lives. This integration has a significant impact on the character of the mahasantri, especially in terms of discipline, responsibility, spirituality, and independence. Thus, Ma'had Putri plays an important role in shaping the character of mahasantri with the Ulul Albab paradigm as a model of integration of religious knowledge and science at UIN Malang. Keywords: Integration of Knowledge, Ma'had Putri, Character of Female Students, UIN Maulana Malik Ibrahim Malang